2015
DOI: 10.1111/mec.13200
|View full text |Cite
|
Sign up to set email alerts
|

More than one genotype: how common is intracolonial genetic variability in scleractinian corals?

Abstract: In recent years, a few colonial marine invertebrates have shown intracolonial genetic variability, a previously unreported phenomenon. Intracolonial genetic variability describes the occurrence of more than a single genotype within an individual colony. This variability can be traced back to two underlying processes: chimerism and mosaicism. Chimerism is the fusion of two or more individuals, whereas mosaicism mostly derives from somatic cell mutations. Until now, it remained unclear to what degree the ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 87 publications
6
89
1
Order By: Relevance
“…Most coral species have clearly adapted to warm environments (54,55) although the time scale of adaptation is likely to be long given the relatively lengthy generation times of corals [3 to 100 years (56)]. Recent studies have shown short-term acclimation and adaptation in some fast-growing species (57) and suggested that some genetic mechanisms may allow faster rates of change (58). It is, however, doubtful that corals will be able to adapt quickly enough to maintain populations under most emissions scenarios (56,59,60), especially where temperature keeps increasing over time (RCP4.5 and higher).…”
Section: Warmingmentioning
confidence: 99%
“…Most coral species have clearly adapted to warm environments (54,55) although the time scale of adaptation is likely to be long given the relatively lengthy generation times of corals [3 to 100 years (56)]. Recent studies have shown short-term acclimation and adaptation in some fast-growing species (57) and suggested that some genetic mechanisms may allow faster rates of change (58). It is, however, doubtful that corals will be able to adapt quickly enough to maintain populations under most emissions scenarios (56,59,60), especially where temperature keeps increasing over time (RCP4.5 and higher).…”
Section: Warmingmentioning
confidence: 99%
“…However, they do exist in long-lived seagrasses clones (Reusch and Boström, 2010) and may confer fitness advantages. Interestingly, in corals, genetic heterogeneity has also been observed within clones (Schweinsberg et al, 2015).…”
Section: A2 Epigenetic Potential To Adapt To Climate Changementioning
confidence: 99%
“…Phenotypically observable mutation rate is similarly high, with 300-500 mutations estimated to accumulate over the lifetime of the colony in Orbicella faveolata (Barfield et al, 2016). High frequencies of somatic mutations have also been proposed to explain significant intra-colonial variability observed in other coral species (Maier et al, 2012;Schweinsberg et al, 2015Schweinsberg et al, , 2016. In addition, significant levels of somatic mutation have been reported in microsatellite loci between ramets within the genet of A. palmata from sites across the Caribbean (Devlin-Durante et al, 2016).…”
Section: (3) Molecular Markers Of Ageing In Coralsmentioning
confidence: 99%